Identification of fish species in some processing products using molecular markers - Thúy Hà, Trần Thị; Hương, Nguyễn Thị; Hương Dịu, Nguyễn Thị; Hưng, Nguyễn Phúc (Vietnam Journal of Biotechnology, 2018)
This study was carried out to identify accurately fish species in the processed fish products by using molecular markers. The nucleotide sequences of the Cytochrome c Oxidase Subunit I gene (COI) of 20 samples from 10 different processed fish products collected in some supermarkets in Hanoi (Big C Long Bien and Aeon Mall Long Bien) were analyzed. The sequences of COI gen were compared to the published data from the National Center for Biotechnology Information (NCBI) and The Barcode of Life Data System (BOLD) in order to determine the similarity. Results showed that there were only forty percents of the total samples with the scientific names matched the names on the packed products. The matched names of fish species between scientific names and packed products at the supermarkets were Salmon Oncorhynchus mykiss, Blue shark Prionace glauca and Tra Pangasius hypophthalmus. Meanwhile, sixty percents of the total samples were identified as mislabeled products. Most of these mislabeled products were found in the products of family Pangasius, from species Pangasius hypophthalmus into species Pangasius bocourti. Although no commercial frauds were found in this study since the price of fish species Pangasius hypophthalmus was cheaper than that of fish species Pangasius bocourti, the correct scientific names of fish species should be labelled for the processed products in order to protect the consumers. The present study also showed that the DNA extraction using a kit Dneasy mericon Food of Qiagen (Germany) and the PCR reaction using Fish and MAB primers were suitable for species identification of processed fish products.